2015
DOI: 10.1002/acr.22584
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Impact of Body Mass Index on the Time Course of Knee Range of Motion, Knee Strength, and Gait Speed After Total Knee Arthroplasty

Abstract: Objective. Quadriceps strength deficits and gait speed limitations remain significant issues after total knee arthroplasty (TKA), yet detailed longitudinal data characterizing these measures and their predictors are limited. This study aimed to describe the time course of knee range of motion, quadriceps strength, and gait speed post-TKA, and to assess whether sex and body mass index (BMI) influenced the time recovery of these measures. Methods. A total of 1,025 patients (mean 6 SD age 67 6 8 years) undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
1
36
0
1
Order By: Relevance
“…A possible explanation for this finding would be higher muscle volume in the slightly to moderately overweight patients, facilitating earlier fulfillment of the strictly functional discharge criteria (Husted 2012 )—whereas the very obese patients might be limited in this by having too much body weight, as one study found postoperative improvements in quadriceps function following TKA to be slower in patients with higher BMIs (Pua et al. 2015 ) and a similar underlying mechanism could explain the same finding in THA. As strictly functional discharge criteria were used, and reduced muscle strength has been identified as being 1 of 3 main reasons for delayed discharge (the other 2 being pain and dizziness), the slower regaining of quadriceps strength may result in delayed functional recovery and therefore in a longer time to discharge (Husted et al.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this finding would be higher muscle volume in the slightly to moderately overweight patients, facilitating earlier fulfillment of the strictly functional discharge criteria (Husted 2012 )—whereas the very obese patients might be limited in this by having too much body weight, as one study found postoperative improvements in quadriceps function following TKA to be slower in patients with higher BMIs (Pua et al. 2015 ) and a similar underlying mechanism could explain the same finding in THA. As strictly functional discharge criteria were used, and reduced muscle strength has been identified as being 1 of 3 main reasons for delayed discharge (the other 2 being pain and dizziness), the slower regaining of quadriceps strength may result in delayed functional recovery and therefore in a longer time to discharge (Husted et al.…”
Section: Discussionmentioning
confidence: 97%
“…14,15,17,18,48,49 In one study, women demonstrated greater improvement than men on Western Ontario and McMaster Universities Arthritis Index (WOMAC) function and pain scores after TKA. 48 Meanwhile, several studies have shown that women score lower and improve less on the Knee Society Score (KSS) after TKA, 14,16,18,50 while other investigations have indicated no sex differences in KSS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Pua et al showed that after TKA, women demonstrate slower recovery of quadriceps strength and gait speed compared to men. 49 However, the strength of the current analysis of sex differences is that we used pre-surgery measures to compare to post-operative time points. Use of change values from the pre-surgical time points adjusted for the well-established differences between sexes as a result of OA and allowed for a more complete evaluation of sex differences with respect to functional trajectories over time.…”
Section: Discussionmentioning
confidence: 99%
“…During each one-to-one rehabilitation session, the physical therapist would review the home exercise program, observe the patients performing the exercises, and correct their form and techniques when necessary. Finally, to monitor treatment progress, patients who attended rehabilitation would undergo a physical assessment involving knee range-of-motion, quadriceps strength, and gait speed testing at 4 weeks and 12 weeks after surgery 8 . Appendix Table II details the inpatient and outpatient rehabilitation programs, and all therapists were trained in the rehabilitation protocols.…”
Section: Exposurementioning
confidence: 99%